Artificial intelligence and agricultural management: Opportunities and risks - Jimenez, Daniel; Muller, Anna; Rhys, Manners; Mariangel, Garcia (2023)
The integration of AI in agricultural management presents a world of opportunities and challenges. We have explored various aspects, from addressing inadequate information and limited capabilities to bridging the digital divide and concerns about job displacement. As we navigate this transformative journey, it is essential to prioritize the user, embrace human-centered design, and ensure that AI-powered solutions are not only feasible but also sustainable for farmers in diverse regions. Moreover, it's vital to recognize the potential of AI to enhance human capacity and improve efficiency rather than solely replacing jobs. Collaboration, open access to information, and co-creation with educational institutions are crucial steps in preparing agricultural professionals for the future. By embracing these opportunities and addressing the associated risks, we can harness the power of AI to accelerate the inclusive and sustainable transformation of agricultural systems, benefiting both farmers and our global food security.